Ian McEwan - Groes, Sebastian (Contemporary critical perspectives series., 2009)
Ian McEwan is one of the most significant, and controversial, British novelists working in the contemporary period. This guide brings together a collection of perspectives on McEwan's oeuvre, not only covering the early works and his writing for the screen but also incorporating detailed and original analyses of the later work.